Learning based on Virtual Class using combination of Second Life and Learning Managment System - Irhamni, Firli; Siradjuddin, Indah Agustien; Kurniawati, Arik; Kusumaningsih, Ari; Triwahyuningrum, Rima (Institut Teknologi Sepuluh Nopember, 2014)
Learning is the most important aspect for increasing the quality of youth generation in a nation. Therefore many learning methods are developed in order to make the youth more qualified. Virtual class based on the second life learning method is proposed in this research. The objective of this learning method is to make learning process more organize and interesting for the youth. There are four stages to build virtual class based on the second life. First, create course material for the learning process. Second, make the virtual class scenario, i.e. student registration, evaluation, and the graduation. Third, design the avatar and the classroom hence the student can get in touch with each other and understand the course material easily. Fourth, build the virtual class based on second life and the scenarios. In this research second life is combined with moodle for learning hence the learning process more interesting and more understandable to the youth